FREQUENCY OF COLOR BLINDNESS AMONGST THE YOUNGEST AGE GROUP IN SOUTHERN PUNJAB PROVINCE OF PAKISTAN: Color Blindness - Fatima, Nauroz; Munawar, Tariq; Fatima, Tanzeel (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine frequency of color blindness and to assess self awareness regarding this ailment amongst the youngest age group in southern Punjab province of Pakistan. Study Design: Cross sectional study. Place and Duration of Study: Combined Military Hospital (CMH) Bahawalpur, from Jan 2016 to Jun 2017. Patients and Methods: Non probability consecutive sampling was done. Candidates who appeared for medical fitness examination were included; all of them belonged to the southern Punjab province of Pakistan. Visual acuity and best corrected visual acuity was assessed. Color vision was checked by using Ishihara color vision charts. Anterior and posterior segment examination of eyes was carried out. Results: Total 1000 candidates underwent color vision assessment. Overall 3.1% (31/1000) of the candidates were found to be color vision deficient. Out of them, 93.54% (29) were unaware of their condition. Conclusion: The screened population showed color blindness to be present in 3.1% of the candidates. Most of the individuals were unaware of the condition.